Efficacy of an immunomodulator compound obtained from Enterococcus faecalis CECT7121 Cell Wall - Confalonieri, Alejandra (2009)
Several studies have demonstrated the utility of the bacterial cell wall extracts (CWE) as immunomodulators on the treatment of some infectious diseases. Enterococcus faecalis (Ef) CECT7121, a probiotic strain, also demonstrated immunomodulation in some animal models. The goal of this work was to obtain an extract of CWE of E. faecalis CECT7121 and to evaluate its efficacy on Salmonella enteritidis (Se) in mice model. Culture died by heat Ef CECT7121 was sonicated during 30 minutes and was put under three successive centrifugations to 27,000g during 1 h. The obtained CWE was freeze-dried. For the efficacy study, thirty Balb-c mice were divided in 3 groups (n=10) and treated as follows: Group I Control: challenged with 2 doses of Se 5x107 CFU/ml (LD99) q12 h and 5 doses of physiological solution q 24h. Group II: received only 5 doses of 1000 μg of CWE q 24h. Experimental Group III: was challenged as Group II and treated with 1000 μg of CWE q 24h. The survival rate was observed during 15 days post- challenge. Thirty percent of the animals of the Group III survived, compared with those of the Group I Control (100% of death). There was not observed changes on health of animals of the Group II, by which demonstrate the safety of the CWE. We conclude that CWE compound would display some immunomodulator properties responsible of the prolongation of the animal survival after challenging with a DL99 of Se.